'They say we are money minded' exploring experiences of formal private for-profit health providers towards contribution to pro-poor access in post conflict Northern Uganda - Justine Namakula; Suzanne Fustukian; Barbara McPake; Freddie Ssengooba (Taylor & Francis Group, 2021)
Background: The perception within literature and populace is that the private for-profit sector is for the rich only, and this characteristic results in behaviours that hinder advancement of Universal health coverage (UHC) goals. The context of Northern Uganda presents an opportunity for understanding how the private sector continues to thrive in settings with high poverty levels and history of conflict. Objective: The study aimed at understanding access mechanisms employed by the formal private for-profit providers (FPFPs) to enable pro-poor access to health services in post conflict Northern Uganda. Methods: Data collection was conducted in Gulu municipality in 2015 using Organisational survey of 45 registered formal private for-profit providers (FPFPs),10 life histories, and 13 key informant interviews. Descriptive statistics were generated for the quantitative findings whereas qualitative findings were analysed thematically. Results: FPFPs pragmatically employed various access mechanisms and these included fee exemptions and provision of free services, fee reductions, use of loan books, breaking down doses and partial payments. Most mechanisms were preceded by managers' subjective identification of the poor, while operationalisation heavily depended on the managers' availability and trust between the provider and the customer. For a few FPFPs, partnerships with Non-governmental organisations (NGOs) and government enabled provision of free, albeit mainly preventive services, including immunisation, consultations, screening for blood pressure and family planning. Challenges such as quality issues, information asymmetry and standardisation of charges arose during implementation of the mechanisms. Conclusion: The identification of the poor by the FPFPs was subjective and unsystematic. FPFPs implemented various innovations to ensure pro-poor access to health services. However, they face a continuous dilemma of balancing the profit maximization and altruism objectives. Implementation of some pro-poor mechanisms raises concerns included those related to quality and standardisation of pricing.